2018
DOI: 10.1007/s40430-017-0922-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryogenic cooling on the surface integrity in hard turning of AISI D6 steel

Abstract: Methods able to enhance surface integrity of machined components have been one of the emerging areas in manufacturing engineering, and a technique that has been providing satisfying results in the last years is cryogenic machining. Besides promoting surface integrity improvement, it is considered an alternative to the use of conventional cutting fluids, which is in accordance with the latest global trends for sustainable means of production. In this sense, replacing grinding operation, which uses large volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Hard turning with cryogenics (i.e. cryogenic machining) helps to remove heat during cutting at a faster rate, which helps to increase tool life and also improves the surface finish [34]. Cryogenic cooling can be performed in three ways.…”
Section: Cutting Fluid and Lubrication Techniquesmentioning
confidence: 99%
“…Hard turning with cryogenics (i.e. cryogenic machining) helps to remove heat during cutting at a faster rate, which helps to increase tool life and also improves the surface finish [34]. Cryogenic cooling can be performed in three ways.…”
Section: Cutting Fluid and Lubrication Techniquesmentioning
confidence: 99%
“…Similarly, Leadebal et al. 22 conducted turning experiments on AISI D6 tool steel under cryogenic condition and reported that surface roughness was reduced around 1.6 times compared to dry machining. Conversely, negative effects of excessive chipping and tool failure were observed while drilling of Inconel 718 using carbide drills.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Dinesh et al, 21 it was observed that cryogenic machining of Zk60 Mg alloy resulted in reduction of 60% of cutting temperature, improving surface finish by 25-40%. Similarly, Leadebal et al 22 conducted turning experiments on AISI D6 tool steel under cryogenic condition and reported that surface roughness was reduced around 1.6 times compared to dry machining. Conversely, negative effects of excessive chipping and tool failure were observed while drilling of Inconel 718 using carbide drills.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous investigations have shown the many benefits of using LN2 as a cutting fluid in the turning of hardened steels instead of dry or conventional flood machining. In most cases these benefits are presented in terms of increased cutting tool life, and consequently decreased tool wear rate, increased workpiece surface hardness and surface compressive residual stresses, and improved surface roughness [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%